Composition of permanences in urban landscape. Plan for Saint-Dié 1945–46 - Gorgeri, Fabiola (Journal of Architecture and Urbanism, 2016)
The relationship between new and existing in urban design is considered by Le Corbusier an opportunity for poetic composition through sequences of visual frames. The public space constitutes the connective tissue and the measure of perceived distance. The buildings are curtains and visual horizons in the territory: they can define the space in which the collective urban scene takes place.Project of soil and perceptive paths allow a paratactical composition of pieces, assembled according to the calibrated balance of spatial proportion; organic dynamicity of the nature and geometric sign refer both to the physical location of the settlement and baggage of historical references culturally shared.From the forties and after Second World War, the urban projects focus more on the consolidated city, or fragments of it, seeking a line of historical continuity with pre-existing environment. There are three kinds of permanences: the geographical aspects, the historical aspects derived from the specific territory and the cultural mnemonic references. So, the plan for Saint-Dié is an expressive example where the city is designed adding analogous shapes: a landscape, an atmosphere, where buildings and environmentterritory resonate mutually.